Sorting Out Australia's New E-cigarette Regulation Policies and Existing Research Gaps - Yundong Yang (International Journal of Public Health and Medical Research, 2026)
With the spread of electronic cigarettes around the world, many countries have implemented various regulations, and Australia has one of the stricter systems globally. Systematically review the new regulations on electronic cigarettes in Australia and focus on the transition to a strict prescription-only system and a wide-ranging ban on non-therapeutic and disposable vaping products. Based on the changes in legislation, the government aims to prevent new smokers among young people at the same time as enabling older smokers to use nicotine e-cigarettes for quitting. Notwithstanding the above measures, implementation problems have arisen, such as the spread of black markets, the unwillingness of general practitioners, and a low compliance rate. Therefore, this paper will outline the current research deficiencies in the above policies. The identified deficiencies are the absence of extended data on how the black market has responded to import bans, the duration over which the medicalised model has been ineffective compared with consumer-regulated models, and the sociocultural causes of illicit youth access. Based on the above analysis, in order to improve the public health situation and promote good policy construction in the future, these deficiencies need to be rectified.